A inclusão de estudantes com deficiência intelectual na educação básica primária da Colômbia: políticas públicas e práticas pedagógicas / Diego Fernando Rosero Ruiz - Ruiz, Diego Fernando Rosero [UNESP] (2015)
The school inclusion of students with disabilities and other special educational needs is a relatively new movement that emerged with remarkable strength in recent decades and that has been the subject of enough controversy, debate and polemic by researchers, academics and other experts in the contemporary educational universe. Currently, there is evidence of some progress in the legislative part of public policies on inclusive education, which has allowed the presence of these students in classrooms, resulting in a significant increase in the number of enrollments of children and adolescents, especially in the field of intellectual disabilities. However, despite advances in the field of inclusive policies and other actions, the pedagogical practices are still not enough disseminated and studied. Given these considerations, the present study aimed to analyze the inclusion of students with intellectual disabilities, as of pedagogical conceptions and practices developed in the processes of teaching and learning in primary basic education in two public schools in a city of Colombia. The study was characterized as a qualitative research of descriptive character. For this, we selected five students who were enrolled in primary basic education, their respective teachers and supporting professionals of each school. Regarding the data collection instruments used, we opted for the systematic observation script, the field diary, the semi-structured interviews and documentary analysis. The theoretical framework supported in the Historic-Cultural Theory and specifically in Vygotsky's contributions. The results showed that most participants expressed certain contradictions and lack of acceptance with reference to the inclusion process, particularly the lack of capacity building and training as well as the lack of support and professional help specializing in their practice. Regarding the conception of intellectual disability, we see concepts strongly...